Analisis Pengaruh Penggunaan Buku Digital (E-Book) Terhadap Minat Dan Kebiasaan Membaca Mahasiswa Universitas Nurul Huda - Zulaikah; Anistya Pratama; Riska Mauliana; Iwan saputra; Shofa, Ghefira Zahira (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
In this digital world, it is no longer taboo that many students and the general public rely more on smartphones which are more practical for reading than carrying books. Digital books are a great way for students to carry lots of books in one hand to study. This research was conducted because it is rare to see students using and reading books in the library, because digital books have become part of students' reading habits. This research was conducted to find out how digital books influence students' reading habits. The subject of this research is a friend of the author who is a student at Nurul Huda University. E-books are a practical form of electronic book that can be carried and accessed anywhere and can be used to support learning and the world of work which is often used in this digital era, so Therefore, this has a big influence on the world of education, including students. From this research we will know whether reading e-books can influence students' reading habits and interest or not. The analytical method used in this research is a qualitative method with a descriptive approach with a collection method. Questionnaire data and interviews are methods that focus on in-depth research and direct immersion in the situation that occurs. The final results of this research contain three main points, namely as follows: 1) E-books can influence students' interest and reading habits 2) E-book reading habits can influence students' literacy knowledge and interest in reading 3) digital books can facilitate and change several habits students in reading because it is easy to carry and can be accessed at any time.